How to Get a Job in Television: Build Your Career from Runner to Series Producer - Sharp, Elsa (Bloomsbury Publishing Plc, 2009)
"Incredibly timely, practical advice for developing contacts and skills" Jo Taylor, 4Talent Manager at Channel 4. Based on the author's experience as a TV researcher, series producer and recruitment executive, this contemporary guide is packed with advice from training bodies, HR executives, and industry professionals.